A low-carbon-oriented multi-time-scale dispatching strategy of multi-energy heterogeneous loads in clean heating scenarios of green residences - Li, Zekun; Sun, Yi; Li, Jiajun; Xiong, Kui; Liang, Siyuan; Shen, Yaqi (Frontiers in Energy Research, 2023)
Clean energy utilization is important for the improvement of energy structure. At present, photothermal and electrothermal conversion technologies are getting prevailing and applied in many residential houses, which can be regarded as green residences. For the heating demand of green residences, solar hot water systems (SHW), electricity-to-heat (E2H) conversion devices such as ground source heat pumps (GSHP), electric heating stoves (EHS) and electric water heaters (EWH) are equipped widely to realize clean heating. Besides, common loads like lighting, washing and electric vehicles (EV) are daily loads in green residences. The above electric load and thermal load are regarded as multi-energy heterogeneous loads (MEHL). To realize the low-carbonization of green residences, MEHL can controlled flexibly to optimize the energy dispatching. In this paper, a novel energy structure of green residences is extended by the combination of SHW, E2H, GSHP, EV as well as roof photovoltaic (RPV). Then, aiming at the minimum carbon emission cost, a residential energy dispatching model is designed from day-ahead (DA) and real-time (RT) scales, and a low-carbon-oriented MEHL coordinated control strategy is proposed. Finally, considering residentials’ comfort loss caused by MEHL control, temperatures of the indoor environment and water tank and EV’s state of charge (SOC) are taken as the special constraints to ensure comfort satisfaction. The simulation shows that the proposed strategy can reduce carbon emission cost by 33.07% and maintain the basic demand for residential heat and electricity consumption. It has good applicability for the low-carbonization of green residences.